PENGARUH PENGGUNAAN MODEL PEMBELAJARAN INTERAKTIF (EXPLICIT INSTRUCTION) TERHADAP KARAKTER DAN HASIL BELAJAR SISWA PADA PEMBELAJARAN TEMATIK MURID - Firdausia, Salsabila; setiawan, Ince Prabu; Maulidnawati, Abrina (Program Studi Pendidikan Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2023)
This study aims to, 1). To find out the description of the interactive learning model on characters and learning outcomes in thematic learning of fourth grade students at SDN 250 Koli-koli, 2). To find out the description of student learning outcomes in thematic learning of fourth grade students at SDN 250 Koli-koli, 3). To find out how the character of students in thematic learning in class IV SDN 250 Koli-koli, 4). To find out whether there is an effect of using interactive learning models on character and learning outcomes in thematic learning of fourth grade students at SDN 250 Koli-koli. The population and sample used in this study used a sampling technique so that 19 students were obtained from the total number of students. . The population and sample used in this study used a sampling technique so that 19 students were obtained from the total number of students. The instrument used is an interactive model questionnaire, to determine the character and student learning outcomes is in the form of a written test in the form of multiple choice questions in the form of pretest and posttest. Based on the results of the normality test, the pretest value was 0.200> 0.05 and the posttest 0.200> 0.05 so that the value of